The evaluation of microbial contamination in the working environment of tanneries - Justyna Skóra; Beata Gutarowska; Łukasz Stępień; Anna Otlewska; Katarzyna Pielech-Przybylska (Nofer Institute of Occupational Medicine, 2014)
Background: Due to their animal material processing, tannery workers may be exposed to biological agents. The aim of the study was the microbial contamination assessment of tanneries with different production specifications. Health risk was estimated based on particle size distribution. Moreover, indicators of microbial contamination of tanneries were selected. Materials and Methods: The studies were conducted in 2 types of tanneries - processing raw hides and producing chrome-tanned leather. Air was sampled with MAS-100 Eco Air Sampler, leathers using RODAC Envirocheck® contact plates and swab method, microbial numbers were determined by a culture method. For the bioaerosols size distribution analysis, a six-stage Andersen sampler was used; identification was performed using microscopy and biochemical methods. Microbial contamination was identified by 16S RNA and ITS1/2 rDNA analysis for bacteria and fungi respectively. Results: The microbial number in the air ranged between 1.2×103 and 3.7×103 CFU/m3. While on the leather, it ranged between 7.6×101 and 5.5×105 CFU/100 cm2. Bacteria dominated in the tanneries (air: 51-92%, leathers: 60-100%). Results indicate that potential health risks arise from the fungal small bioaerosol particles presence (0.65-2.1 μm). Eleven indicator microorganisms were determined: B. pumilus, B. subtilis, B. cereus, C. lubricantis, C. cladosporioides, P. commune, P. echinulatum, P. chrysogenum, P. crustosum, C. parapsilosis and C. albidus. Conclusions: Microbial contamination evaluation in the tanneries showed the increased bacteria and fungi number in the air in relation to the outdoor air, which indicates an occupational inhalation risk to workers. The designated indicators of microbial contamination in the tanneries are associated with their specific and potentially pathogenic working environment. Med Pr 2014;65(1):15-32